PENENTUAN KEDALAMAN SUMUR BOR BERDASARKAN DATA GEOLISTRIK RESISTIVITAS DI BEBERAPA KAMPUNG DI KABUPATEN FAK-FAK - Khristian Enggar Pamuji (FMIPA Universitas Papua, 2018)
Geoelectrical Resistivity method is a geophysical method that can be used to determine subsurface geology based on rock resistivity image. Resistivity survey has been done in some villages, in Fak Fak Regency, West Papua Province. The measurement method that used is sounding, whereas electrode configuration used is Dipole-dipole configuration with a stretch of 100 -150 m. The data obtained are then processed by Progress Res2Dinv. The results of this survey obtained show that in the resistivity sounding measurement point found any good groundwater aquifers, as the water source of drilled well. Water layer with the thickness between 1-3 m at the surface (alluvial) is a rain water infiltration that is not recommended to make boreholes at this point.